Child Neurodevelopmental Outcomes by Prepregnancy Body Mass Index and Gestational Weight Gain. Issue 6 (December 2018) - Kominiarek, Michelle A.; Smid, Marcela C.; Mele, Lisa; Casey, Brian M.; Sorokin, Yoram; Reddy, Uma M.; Wapner, Ronald J.; Thorp, John M.; Saade, George R.; Tita, Alan T. N.; Rouse, Dwight J.; Sibai, Baha; et al.
Abstract : OBJECTIVE: To study the association of prepregnancy body mass index (BMI) and gestational weight gain with child neurodevelopmental outcomes. METHODS: We performed a secondary analysis of data from two parallel, multicenter, randomized, double-blind, placebo-controlled thyroxine replacement trials in pregnant women with either hypothyroxinemia or subclinical hypothyroidism who delivered at term. Body mass index was categorized as normal (18.5–24.9), overweight (25.0–29.9), or obese (30 or greater). We also evaluated early (20 weeks of gestation or less), late (greater than 20 weeks of gestation), and total gestational weight gain and categorized gestational weight gain as inadequate, adequate, and excessive per 2009 Institute of Medicine guidelines. Neurodevelopmental outcomes included 5-year Wechsler Preschool and Primary Scale of Intelligence and 3-year Differential Ability Scales-II. Linear and logistic regression analyses were performed and adjusted for maternal age, race–ethnicity, education, insurance status, parity, smoking and alcohol use, thyroid status (subclinical hypothyroidism or hypothyroxinemia), treatment group, gestational age at delivery, and neonatal sex. RESULTS: Of the 948 women included, 380 (40%), 305 (32%), and 263 (28%) had normal, overweight, and obese prepregnancy BMI, respectively. A total of 106 (11%), 212 (22%), and 630 (66%) of women had inadequate, adequate, and excessive total rates of gestational weight gain, respectively. Maternal differences among the BMI categories included race–ethnicity, education, insurance type, parity, and thyroid status (all P <.01), whereas the gestational weight gain groups only differed by parity ( P <.001). In unadjusted analysis, children of obese (93.2±12.8; 88.5±13.3) and overweight (94.1±15.6; 89.6±16.0) women had lower Wechsler Preschool and Primary Scale of Intelligence and Differential Ability Scales-II scores, respectively, than normal-weight women (97.4±15.4; 93.9±16.0; P <.001 for all comparisons); however, in adjusted analysis, there were no differences in neurodevelopmental outcomes by maternal BMI. The association was primarily accounted for by race–ethnicity and education. In unadjusted and adjusted analyses, there were no differences in neurodevelopmental outcomes by adequacy of early, late, or total gestational weight gain. CONCLUSION: In women with either subclinical hypothyroidism or hypothyroxinemia, neither prepregnancy BMI nor gestational weight gain was associated with neurodevelopmental outcomes among children born at term in adjusted analyses. Abstract : Maternal prepregnancy body mass index and gestational weight gain are not associated with child neurodevelopmental outcomes.